SALAFI THOUGHT AS THE BASIS OF COUNTER-RADICALISM: AN EMPIRICAL STUDY OF KPI ALUMNI OF STAI AS-SUNNAH KPI IN THE PERSPECTIVE OF ISLAMIC LAW: PEMIKIRAN SALAFI SEBAGAI BASIS KONTRA-RADIKALISME: STUDI EMPIRIS TERHADAP ALUMNI KPI STAI AS-SUNNAH DALAM PERSPEKTIF HUKUM ISLAM - Hamdani Hamdani; Zulkarnain Zulkarnain; Dhiauddin Tanjung (SOSIOEDUKASI, 2025)
This study aims to analyze the contribution of Salafi understanding among alumni of the Islamic Communication and Broadcasting (KPI) Program at STAI As-Sunnah Tanjung Morawa in countering terrorism-related ideologies in Indonesia. Amid the widespread dissemination of radical ideologies, especially among youth through social media and educational institutions, authentic Salafi teachings offer a moderate and non-violent religious approach. Although STAI As-Sunnah does not formally identify itself as a Salafi institution, the educational and preaching orientation of its alumni reflects a strong adherence to the values of the Salafus Shalih. This research adopts a quantitative approach using a correlational method. A sample of 35 alumni was selected through purposive sampling, and data were collected via a closed-ended questionnaire that had been tested for validity and reliability. The findings indicate that alumni possess a very high level of Salafi understanding, accompanied by a strong attitude against terrorism. There is a very strong correlation between Salafi understanding and anti-terrorism attitudes, with the former significantly contributing to ideological resilience against radicalism. The study concludes that proper and balanced Salafi understanding plays a vital role in shaping moderate religious attitudes and supports deradicalization efforts within the Indonesian Muslim community, particularly among the younger generation.